Organic and conventional alternative curing ingredients effects on quality and sensory attributes of deli-style Turkey - Siyuan Sheng; Erin M. Silva; Steven C. Ricke; James R. Claus (Poultry Science, 2025)
Deli-style turkey breast products were cured with sodium nitrite (SN), pre-converted conventional grown celery (CEL), Swiss Chard (SC), organic grown celery (OCEL), and organic Swiss Chard (OSW) with an ingoing sodium nitrite equivalent of 150 ppm and salt content of 1.60 %. Cured and total meat pigments, total myoglobin content, and salt content were assessed on day 0; color, pH, and residual nitrite were evaluated on days 0, 15, 30, 45, and 60. A 24-h color depletion study was conducted on all treatments (TRTs) after storage (day 15). Consumer panelists were recruited to evaluate sensory attributes of all TRTs. During the storage and light display, SN exhibited the lightest color and the lowest (P < 0.05) levels of yellowness. At 0 h, Celery TRTs demonstrated lower (P < 0.05) hue angle compared to Swiss chard TRTs. This color difference gradually becomes unnoticeable by the conclusion of the test. Furthermore, the choice between organic and non-organic curing does not affect the color of the finished products. Sensory results indicated that OSW exhibited greater earthiness (P < 0.05) than all other TRTs, except for CEL, which showed no significant difference (P > 0.05). Sensory evaluation results also indicated that OSW displayed the greatest non-meat aftertaste (P < 0.001) than all other TRTs and lower bitterness (P = 0.009) than SN. However, regardless of the different plant sources of nitrite (Celery or Swiss Chard) and growing practice of plant powder (conventional or organic), sensory evaluation found that these alternative cures were equivalent (P > 0.05) to SN in overall liking difference and relevant purchase intent. Volatile compounds (VOCs) analysis revealed a distinctively different distribution of VOCs among the different sources of nitrite. The presence of terpene alcohol and lower abundance of aldehydes in OSW could explain the findings identified in the sensory evaluation.